The risk of typhoon and storm surge along the coast of Vietnam - Thuy, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2019)
The history (1951–2016) and the risk of typhoon and storm surge in coastal areas of Vietnam are analyzed and evaluated based on the observation data, results of statistical and numerical models. The Monte Carlo method was used to construct a bogus typhoon. A coupled numerical model of Surge, Wave and Tide (called SuWAT) was used for simulation of storm surge. The results show that in the period of 1951–2016 there were many typhoons which landed and induced high storm surge on the coast of the North and the North of Center of Vietnam. During one thousand years, there have been 4,678 typhoons entering the coastal zone from Quang Ninh to Ca Mau. In particular, the most severe typhoon in coastal area from Quang Ninh to Thanh Hoa is at level 16 (Beaufort scale), Nghe An - Quang Tri at level 16, Quang Binh - Phu Yen at level 17, Binh Dinh - Ninh Thuan at level 15 and Binh Thuan - Ca Mau at level 13. The coastal areas with highly vulnerable storm surge are provinces from Quang Ninh to Hai Phong (4.5 m), Thanh Hoa to Nghe An (4.0 m), Quang Tri (5.0 m). The results of this study are the basis for the preparation to cope with strong/super typhoon in the coast of Vietnam.